ChemInform Abstract: Palladium Nanoparticles Supported on Ionic Liquid Modified, Magnetic Nanobeads — Recyclable, High‐Capacity Catalysts for Alkene Hydrogenation. Issue 46 (18th November 2014) - Linhardt, Roland; Kainz, Quirin M.; Grass, Robert N.; Stark, Wendelin J.; Reiser, Oliver
Abstract Magnetically recoverable hybrid materials consisting of Pd‐nanoparticles supported on magnetic cobalt‐carbon nanobeads functionalized with imidazolium‐based ionic liquid are synthesized and their activity for the catalytic hydrogenation of olefins and nitroarenes is demonstrated.